PERENCANAAN DERMAGA PELABUHAN TANJUNG BONANG REMBANG - Rizqi Maulana Wijaya; Purwanto Purwanto; Priyo Nugroho P. (Jurnal Karya Teknik Sipil, 2014)
Jetty Tanjung Bonang Rembang Port located on the coast of Sendangmulyo Village, Sluke Sub District, Rembang District, Central Java Province. This jetty construction is aiming to serve 10,000 DWT general cargo ship and to maximize distribute goods in the area of Rembang and surroundings. In order to support this jetty is needed planning for a navigation channel, port basin, breakwaters, as well as dimensions and structure of the jetty along with the attributes. Navigation channel of Tanjung Bonang Rembang Port is planned facing towards Northeast with depth that is used at least -10.5 m, navigation channel width is taken by 137 m and port basin depth is -10 m. The type of breakwaters structure is rubblemound breakwaters for the west side and east side. The structure of jetty is used local cast reinforced concrete with strength of concrete f'c = 35 MPa. Foundation structure are using steel piles with quality JIS A5525, SKK 400, fy’ = 2,350 kg/cm2. In the planning of this jetty, system structure is analyzed by using the program SAP 2000 with 3D models. Load and reinforce structures is controlled by SNI regulations and BMS 1992. From the designing plan result is obtained that jetty consists of a jetty head and 2 trestle. The dimension of jetty head is 170 m length and 22 m width, while the dimension of trestle is 26 m length and 10 m width. The jetty beam dimension is 40 cm width and 60 cm height, while the pile dimension is 45 cm diameter, 1.2 cm thickness, and 20.65 m length for vertical pile and 20.75 m length for diagonal piles with slope ratio 10 V: 1 H. Pile cap dimension for single pile on jetty head and trestle is 1 x 1 x 1.5 m. Pile cap dimensions for double pile on jetty head is 1.5 x 1 x 1.5 m, and pile cap dimensions for the edge of jetty head is 1.6 x 1.2 x 2.6 m. On the berthing structure is used Fentek Arch Fender-type AN 600 L = 2,500 mm and the mooring structure is used Bollard and Bitt with a capacity 50 tons.